2018
DOI: 10.1142/s2010135x18300025
|View full text |Cite
|
Sign up to set email alerts
|

Flexoelectricity in dielectrics: Materials, structures and characterizations

Abstract: Flexoelectricity in dielectrics suggests promising smart structures for sensors, actuators and transducers. In this review, dielectric materials, structures and the associated flexoelectric characterization methods are presented. First of all, we review structures and methods to measure different flexoelectric coefficients, including [Formula: see text], etc., via direct or converse flexoelectric effect. The flexoelectric materials in the form of bulk, thin films and 2D materials and the reported flexoelectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 87 publications
0
27
0
Order By: Relevance
“…The flexoelectric coefficients of most dielectric solids, especially the simple ones, are estimated theoretically to be too small ,, to induce sufficient strain gradient for mechanical switching. Particularly, flexoelectricity can be omitted when other electromechanical responses (e.g., piezoelectricity) exist in the materials. , However, it was later found that in some dielectrics owning to high permittivity, their flexoelectricity is unexpectedly largely enhanced and possibly sufficient to induce polarization, , where the flexoelectric coefficients are in several or even tens of orders of higher magnitude. These reported high permittivity dielectrics with giant flexoelectricity include paraelectric SrTiO 3 , and perovskite piezoelectrics, especially perovskite relaxors such as PMN, , perovskite ferroelectrics such as Pb-based systems like Pb­(Zr,Ti)­O 3 , , BaTiO 3 -based systems like BaTiO 3 , , Ba­(Ti,Sn)­O 3 , BaTiO 3 –Ba­(Zr,Ti)­O 3 , and (K,Na)­NbO 3 -based systems, and perovskite relaxor ferroelectrics like PMN–PT ,, and PIN–PMN–PT . According to Tagantsev’s flexoelectric theory, , the possible mechanisms of these enhanced flexoelectricity in bulks include four contributions: dynamic bulk flexoelectricity, static bulk flexoelectricity, surface flexoelectricity, and surface piezoelectricity. , The mechanisms of a barrier layer, inner microstrains resulted from macroscopic centric symmetry breaking, ferroelectricity, , and PNRs , are also proposed recently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flexoelectric coefficients of most dielectric solids, especially the simple ones, are estimated theoretically to be too small ,, to induce sufficient strain gradient for mechanical switching. Particularly, flexoelectricity can be omitted when other electromechanical responses (e.g., piezoelectricity) exist in the materials. , However, it was later found that in some dielectrics owning to high permittivity, their flexoelectricity is unexpectedly largely enhanced and possibly sufficient to induce polarization, , where the flexoelectric coefficients are in several or even tens of orders of higher magnitude. These reported high permittivity dielectrics with giant flexoelectricity include paraelectric SrTiO 3 , and perovskite piezoelectrics, especially perovskite relaxors such as PMN, , perovskite ferroelectrics such as Pb-based systems like Pb­(Zr,Ti)­O 3 , , BaTiO 3 -based systems like BaTiO 3 , , Ba­(Ti,Sn)­O 3 , BaTiO 3 –Ba­(Zr,Ti)­O 3 , and (K,Na)­NbO 3 -based systems, and perovskite relaxor ferroelectrics like PMN–PT ,, and PIN–PMN–PT . According to Tagantsev’s flexoelectric theory, , the possible mechanisms of these enhanced flexoelectricity in bulks include four contributions: dynamic bulk flexoelectricity, static bulk flexoelectricity, surface flexoelectricity, and surface piezoelectricity. , The mechanisms of a barrier layer, inner microstrains resulted from macroscopic centric symmetry breaking, ferroelectricity, , and PNRs , are also proposed recently.…”
Section: Resultsmentioning
confidence: 99%
“…According to Tagantsev’s flexoelectric theory, , the possible mechanisms of these enhanced flexoelectricity in bulks include four contributions: dynamic bulk flexoelectricity, static bulk flexoelectricity, surface flexoelectricity, and surface piezoelectricity. , The mechanisms of a barrier layer, inner microstrains resulted from macroscopic centric symmetry breaking, ferroelectricity, , and PNRs , are also proposed recently. In relaxor ferroelectrics such as PMN–PT, PIN–PMN–PT single crystal, it is believed that polar nanodomain rotation polarization, , residual piezoelectricity, surface piezoelectricity, and surface flexoelectricity can give rise to these enhanced flexoelectric behaviors. Notably, the PNRs are reported to be one important source of the residual flexoelectricity. , Besides, PNRs are in dominant contribution (50–80%) to the room-temperature ultrahigh piezoelectricity in relaxor ferroelectric solid solution crystals, which can facilitate polarization rotation and enhance ferroelectricity/piezoelectricity and thus couple extrinsically , with their flexoelectricity.…”
Section: Resultsmentioning
confidence: 99%
“…The flexoelectric effect is a phenomenon in which the gradient of material alignment induces electric polarization . The piezoelectric effect differs from the flexoelectric effect as polarization is induced by uniform displacement in the piezoelectric effect. , The flexoelectric effect appears in various materials, such as ceramics, polymers, biological thin films, and liquid crystals (LCs). , There have been studies using this effect for electrical energy harvesting, actuators, and sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, only a few polymers exhibit significant piezoelectricity (Bauer and Bauer, 2008). Thus, quantifying flexoelectricity at large deformations may enable the design of efficient electromechanical elastomeric devices, such as sensors, actuators and energy harvesters, based on the flexoelectric effect (Jiang et al, 2013, Huang et al, 2018, Wang et al, 2019.…”
Section: Introductionmentioning
confidence: 99%